2013
DOI: 10.1111/pme.12100
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Opioid Misuse among Patients with Cancer Pain Using the SOAPP-SF

Abstract: Patients classified by the SOAPP-SF in the current study as high risk tended to be younger, endorse more pain, have higher MEDD requirement, and endorse more symptoms of depression and anxiety. These findings are consistent with the literature on risk factors of opioid abuse in chronic pain patients which suggests that certain patient characteristics such as younger age, anxiety, and depression symptomatology are associated with greater risk for opioid misuse. However, a limitation of the current study is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 29 publications
5
83
0
6
Order By: Relevance
“…shown that anxiety and depression can have negative effects on pain and an increased risk of misusing opioids [6,33,34]. However, as mentioned, there is a lack of research regarding the mediating effects of depression and anxiety in the relationship between pain and prescription opioid misuse.…”
Section: Discussionmentioning
confidence: 95%
“…shown that anxiety and depression can have negative effects on pain and an increased risk of misusing opioids [6,33,34]. However, as mentioned, there is a lack of research regarding the mediating effects of depression and anxiety in the relationship between pain and prescription opioid misuse.…”
Section: Discussionmentioning
confidence: 95%
“…8 Furthermore, there is sparse literature regarding the use and implementation of screening tools in the treatment of cancer pain. 9,10 One study reported the implementation of the SOAPP-short form (SOAPP-SF). 10 The SOAPP-SF is an abbreviated 5-item self-report that was created, in part, to reduce the time burden of patients in completing the 14-item SOAPP questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…The SOAPP-R may be the most effective at predicting aberrance according to recent studies, but all screening tests are more helpful when interpreted in clinical context [58]. The SOAPP-SF (short-form version) has also been shown to be an effective screening tool, and, with only five items, is easy to incorporate into the clinical interview [59]. Consistency in using the same screener in the same manner for all patients and then appropriately interpreting the result is important, so each provider or clinical setting should determine the instruments most suited to their situation and become adept in their use.…”
Section: Addiction Risk Assessmentmentioning
confidence: 97%